Protection for Women with Disabilities Who Are Victims of Sexual Violence - Wahyuni, Wahyuni; Muharuddin , Muharuddin (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to examine the legal protection provided to women with disabilities who are victims of sexual violence in Sorong City and to identify various obstacles encountered in the implementation of such protection. This study uses an empirical legal method with data obtained through literature studies and interviews, which are then analyzed using an empirical legal approach to the implementation of protection for women with disabilities who are victims of sexual violence in Sorong City. The novelty of this study lies in its focus on the implementation of legal protection for women with disabilities who are victims of sexual violence in Sorong City. The results of the study show that (1) legal protection for women with disabilities who are victims of sexual violence in Sorong City is not yet optimal. There are no specific regulations at the local level that specifically regulate persons with disabilities. Although protection services for victims are available, their implementation is still limited. (2) Some of the obstacles faced include a lack of professionals such as psychologists and specialized interpreters, difficulties for victims in providing consistent statements, and a lack of preparedness among law enforcement officials in handling cases where the victim is a person with disabilities. The study's conclusions on legal protection for persons with disabilities who are victims of sexual violence in Sorong City indicate that there have been significant efforts by the government and related institutions. Although there is a legal framework that guarantees the rights of persons with disabilities, such as Law No. 8 of 2016, implementation in the field is still hampered by a lack of training for law enforcement officers, as well as a lack of supporting resources such as professional personnel and communication aids.